Mechanistic understanding and potential application of electrospraying in food processing: a review. Issue 30 (7th November 2022) - Dhiman, Atul; Suhag, Rajat; Singh, Arashdeep; Prabhakar, Pramod K.
Abstract: Electrospraying (ESPR) is a cost effective, flexible, and facile method that has been used in the pharmaceutical industry, and thanks to its wide variety of uses such as bioactive compound encapsulation, micronization, and food product coating, which have received a great attention in the food market. It uses a jet of polymer solution for processing food and food-derived products. Droplet size can be extremely small up to nanometers and can be regulated by altering applied voltage and flow rate. Compared to conventional techniques, it is simple, cost effective, uses less solvent and products are obtained in one step with a very high encapsulation efficiency (EE). Encapsulation provided using it protects bioactives from moisture, thermal, oxidative, and mechanical stresses, and thus provides them a good storage stability which will help in increasing the application of these ingredients in food formulation. This technique has an enormous potential for increasing the shelf life of fruit and vegetables through coating and improvement of eating quality. This study is aimed at overviewing the operating principles of ESPR, working parameters, applications, and advantages in the food sector. The article also covers new ESPR techniques like supercritical assisted ESPR and ESPR assisted by pressurized gas (EAPG) which have high yield as compared to conventional ESPR. This article is enriched with good information for research and development in ESPR techniques for development of novel foods.